2014
DOI: 10.1002/lary.25062
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and quality‐of‐life outcomes following gland‐preserving surgery for chronic sialadenitis

Abstract: 4.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
107
2
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(117 citation statements)
references
References 10 publications
7
107
2
1
Order By: Relevance
“…The use of a questionnaire to specifically characterize obstructive sialadenitis symptoms and the impact of sialendoscopy‐assisted salivary duct surgery is a novel effort. General surveys such as the SF‐36 or SF‐8 and the Glasgow Benefit Inventory demonstrate changes in general QOL measures but have limitations in measuring specific symptom changes. Other otolaryngology‐based disease‐specific questionnaires such as the Rhinoplasty Outcomes Evaluation, the Sino‐Nasal Outcome Test, and the Tinnitus Functional Index significantly impact the ability to study treatment effectiveness.…”
Section: Discussionmentioning
confidence: 99%
“…The use of a questionnaire to specifically characterize obstructive sialadenitis symptoms and the impact of sialendoscopy‐assisted salivary duct surgery is a novel effort. General surveys such as the SF‐36 or SF‐8 and the Glasgow Benefit Inventory demonstrate changes in general QOL measures but have limitations in measuring specific symptom changes. Other otolaryngology‐based disease‐specific questionnaires such as the Rhinoplasty Outcomes Evaluation, the Sino‐Nasal Outcome Test, and the Tinnitus Functional Index significantly impact the ability to study treatment effectiveness.…”
Section: Discussionmentioning
confidence: 99%
“…The only publication describing patient acceptance after treatment for salivary duct stenoses was mentioned earlier 40 . Several authors assessed patient satisfaction after sialendoscopic controlled therapy of obstructive sialadenitis, not exclusively including patients with duct stenosis 53 55 56 88 . Kroll et al, using the Short Form 36 (SF-36) questionnaire, found a high level of patient satisfaction 53 .…”
Section: Treatmentmentioning
confidence: 99%
“…Kroll et al, using the Short Form 36 (SF-36) questionnaire, found a high level of patient satisfaction 53 . Gillespie et al using a salivary-specific standardised questionnaire (modified OHIP-14 scores) observed that the scores after treatment of cases not caused by sialolithiasis improved, but significantly less than the scores after treatment for sialolithiasis, with significantly less improvement in salivary gland-related quality of life scores 55 . Similar results were obtained by Aubin-Pouliot et al, who used a questionnaire designed to obtain a chronic obstructive sialadenitis score (COSS).…”
Section: Treatmentmentioning
confidence: 99%
“…As a surgical procedure needs to be assessed on the basis of objective surgical and subjective patient perceived results measured using validated questionnaires 15 , the aim of this study was to assess the surgical, US and subjective outcomes in a large series of patients who underwent trans-oral removal of a large HPSMS and who were followed in the long term.…”
Section: Introductionmentioning
confidence: 99%